Pengembangan Media Pembelajaran Google Site Materi Perubahan Iklim untuk Kelas 10 MA Al-Fattahiyyah - Ayu Siti Nur Afifah; Fahrur Rozy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Several tenth-grade students at MA Al-Fattahiyyah perceive physics as a difficult and uninteresting subject. Current conventional teaching methods require innovation to boost student motivation. To address this, interactive learning media using Google Sites is proposed to create a more engaging and active learning environment. This study aims to develop a valid and feasible learning medium on climate change for tenth-grade students at MA Al-Fattahiyyah. The research employs a Research and Development (R&D) method, using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The content aligns with the school's current instructional modules. Participants include two media experts, one subject matter expert, and tenth-grade students. Research instruments include interview guidelines, validation checklists, and user response questionnaires. Validation by the two media experts yielded scores of 82 percent and 97 percent, while the subject expert gave 88 percent. Field testing with small and large groups of students showed scores of 90 percent and 91 percent, respectively. The average score was 90 percent, indicating the media is “Highly Valid”. These results show that the developed media is suitable for classroom use and can enhance the quality of physics instruction by making learning more interactive, engaging, and pedagogically effective.